Mechanical Stress Results in Immediate Accumulation of Glucosinolates in Fresh-Cut Cabbage - Tomaž Požrl; Blaž Cigić; Lea Demšar; Janez Hribar; Tomaž Polak (Journal of Chemistry)
The intensity of mechanical stress and the temperature significantly affect the levels of individual and total glucosinolates in shredded white cabbage (cv. Galaxy). Mild processing (shredding to 2 mm thickness) at 8°C resulted in the accumulation of glucosinolates (40% increase) in comparison with unshredded cabbage, which was already seen 5 min after the mechanical stress. Severe processing (shredding to 0.5 mm thickness) at 20°C, however, resulted in an initial 50% decrease in glucosinolates. The glucosinolates accumulated in all of the cabbage samples 30 min from processing, resulting in higher levels than in unshredded cabbage, except for the severe processing at 20°C where the increase was not sufficient to compensate for the initial loss. Glucobrassicin and neoglucobrassicin were the major glucosinolates identified in the cabbage samples. Mechanical stress resulted in an increase in the relative proportion of glucobrassicin and in a decrease in neoglucobrassicin.